Stress-strain relationship of translucent nanocrystalline Gadolinium Zirconate ceramic with grain size below 10 nm using nanoindentation. Issue 6 (15th April 2020) - Wang, Haomin; Huang, Zhangyi; Deng, Jirui; He, Duanwei; Qi, Jianqi; Lu, Tiecheng; wang, Qingyuan
Abstract: Translucent nanocrystalline Gadolinium Zirconate (Gd2 Zr2 O7 ) ceramic with grain size below 10 nm was successfully fabricated using high pressure sintering technology at 5 GPa and low temperature of 550 °C. The bilinear compressive stress-strain relationship of this sample was firstly extracted from nanoindentation procedure based on the partial unloading method. It indicated that the plastic deformation did not originate from dislocation sliding and was controlled by the grain boundary sliding. Moreover, the compressive yield strength, σ y = 7.8  GPa of the translucent nanocrystalline Gd2 Zr2 O7 ceramic was also determined by the intersection of the theoretical elastic line and the indentation compressive stress-strain line.